Appropriate nutrient supplementation in celiac disease. (December 2013) - Caruso, Roberta; Pallone, Francesco; Stasi, Elisa; Romeo, Samanta; Monteleone, Giovanni
Abstract Reduced levels of iron, folate, vitamin B12, vitamin D, zinc, and magnesium are common in untreated celiac disease (CD) patients probably due to loss of brush border proteins and enzymes needed for the absorption of these nutrients. In the majority of patients, removal of gluten from the diet leads to histological recovery and normalization of iron, vitamin, and mineral levels. Iron deficiency anemia is the most common extra-intestinal sign of CD and usually resolves with adherence to a gluten-free diet. However, deficiencies of both folate and vitamin B12 may persist in some patients on a gluten-free diet, thus requiring vitamin supplementation to improve subjective health status. Similarly, exclusion of gluten from the diet does not always normalize bone mineral density; in these cases, supplementation of vitamin D and calcium is recommended. Resolution of mucosal inflammation may not be sufficient to abrogate magnesium deficiency. Since gluten-free cereal products have a lower magnesium content as compared with gluten-containing counterparts, a magnesium-enriched diet should be encouraged in CD patients. In this article we discuss the frequency and clinical relevance of nutrient deficiency in CD and whether and when nutrient supplementation is needed.